Analysis of Community Economic Empowerment through Village-Owned Enterprises in Bumi Merapi Village, Baradatu District, Way Kanan Regency - Nufi M Yusuf; Finny Ligery; M Agus Mushodiq (LP2M IAIN Palopo, 2026)
This study is motivated by the gap between the theoretical concepts of community economic empowerment and their implementation in the field through Village-Owned Enterprises (BUMDes). Although BUMDes Duta Merapi in Kampung Bumi Merapi, Baradatu District, Way Kanan Regency, has implemented various empowerment programs, unequal community participation, limited human resource capacity, and restricted access to information and capital have resulted in suboptimal empowerment outcomes. This study aims to analyze the process of community economic empowerment through BUMDes and to identify its supporting and inhibiting factors, including from the perspective of Islamic economics. This research employs a qualitative approach with a descriptive-evaluative design. Data were collected through observation, semi-structured interviews, and documentation involving informants consisting of the Village Head, BUMDes management, and community members who utilize BUMDes services. Data analysis was conducted inductively through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings indicate that community empowerment is implemented through three main stages: awareness-building, capacity building, and resource utilization, followed by continuous evaluation. The results show that BUMDes Duta Merapi has improved community access to economic services, encouraged the emergence of new small businesses, and strengthened public trust in village institutions. The novelty of this study lies in the finding that empowerment effectiveness is not solely determined by economic and institutional aspects, but also by the quality of multi-channel communication, village leadership interaction, and the integration of Islamic ethical-spiritual values. Supporting factors include village government support, a clear organizational structure, and the use of digital media, while inhibiting factors include low digital literacy, limited human resource capacity, and uneven community participation. This study recommends strengthening strategic collaboration between BUMDes, local governments, Islamic financial institutions, as well as improving human resource capacity and optimizing marketing networks to enhance the sustainability of rural economic empowermen